Factors Affecting the Nutritional Status of Pregnant Women with Low Birth Weight in the Work Area In Panyabungan Jae Health Center, Penyabungan District, Mandailing Regency City Natal 2022 - Dwi Ris Hasanah S. (Sean Institute, 2023)
Pregnancy is an important period of life. At that time the mother must prepare herself as well as possible to welcome the birth of her baby. WHO (Word Health Organization), states that the prevalence of LBW in the world is 20 million (15.5%) annually, and developing countries are the largest contributor, which is around 96.5%. This research is an analytic survey with a cross sectional approach. The research population was 72 people. A sample of 43 respondents using the Random Sampling technique, namely the total population that will be used as a population. The research instrument uses Primary Data (Questionnaire) which consists of 20 questions. The independent variable in this study was the nutritional status of pregnant women with low birth weight. And the dependent variable of this study is age, occupation, education, parity, source of information. The results of the study were that most of the mothers, as many as 20 people (44.4%) of respondents had less status. The results of the chi-squer test obtained a p-value of 0.030 <0.05 so that Ho was rejected and Ha was accepted. In this study, there are factors that affect the nutritional status of pregnant women with low birth weight in the Work Area of ​​the Panyabungan Jae Health Center, Panyabungan District, Mandailing Natal District. It is hoped that the cooperation of health workers, cadres and parents will fulfill balanced nutrition in toddlers to avoid LBW. In this study, there are factors that affect the nutritional status of pregnant women with low birth weight in the Work Area of ​​the Panyabungan Jae Health Center, Panyabungan District, Mandailing Natal District. It is hoped that the cooperation of health workers, cadres and parents will fulfill balanced nutrition in toddlers to avoid LBW. In this study, there are factors that affect the nutritional status of pregnant women with low birth weight in the Work Area of ​​the Panyabungan Jae Health Center, Panyabungan District, Mandailing Natal District. It is hoped that the cooperation of health workers, cadres and parents will fulfill balanced nutrition in toddlers to avoid LBW.